2018
DOI: 10.1590/abd1806-4841.20186726
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Gianotti-Crosti syndrome

Abstract: We report the case of a male 22-month-old child, with atypical presentation of Gianotti-Crosti syndrome after infection with Epstein-Barr virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…Moreover, previous studies reported an atypical clinical presentation in GCS not associated with hepatitis B, characterized by a polymorphic eruption of erythematous or purpuric papules, vesicles and blisters asymmetrically distributed, frequently coalescing forming large edematous and pruritic lesions [ 16 , 17 ]. Admittedly, this was consistent with our case.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported an atypical clinical presentation in GCS not associated with hepatitis B, characterized by a polymorphic eruption of erythematous or purpuric papules, vesicles and blisters asymmetrically distributed, frequently coalescing forming large edematous and pruritic lesions [ 16 , 17 ]. Admittedly, this was consistent with our case.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the patient did not have any history of drugs intake or family allergy. GCS occurrence was also described after vaccination against polio, influenza, hepatitis B, and DPT vaccine (diphtheria, tetanus, and pertussis) 5,13,16 but the patient did not receive any recent vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many GCS cases preceded by vaccination have also been reported. 1,[8][9][10] Vaccines associated with GCS are as following Haemophilus influenza type b (Hib); oral polio; diphtheria, pertussis, and tetanus (DPT); measles, mumps, and rubella (MMR); bacillus Calmette-Guerin (BCG); hepatitis B and A, and Japanese encephalitis. 1,5,9,11 It was reported in the literature that 21 out of 300 GCS cases were associated with vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy may be considered if the skin lesions persist for more than 6 months or GCS cases with atypical presentation and exclude the differential diagnosis in high-risk or immunocompromised patients. 1,2,10 Histopathological features are nonspecific showed parakeratosis of the epidermis, focal spongiosis, mild acanthosis, and psoriasiform epidermal hyperplasia. Perivascular lymphohistiocytic infiltrate with scattered eosinophils and extravasation of erythrocytes in the dermis.…”
Section: Discussionmentioning
confidence: 99%